Impact of Self-Motivation on the Academic Performance of University Students: A Comparative Study of Male and Female Students of University of Education D. G. Khan Campus - Raheem, Muhammad Arslan; Naz, Samina; Nasir, Muhammad (Annals of Human and Social Sciences, 2024)
The paper aims to investigate how differently self-motivation affects the academic performance of male and female students at university level. In the view of said aim of the study, BS- level male and female students from four Natural Sciences departments of the University of Education Lahore, D. G. Khan Campus were selected for data collection purpose. In order to measure self-motivation, a questionnaire was crafted and to gather academic performance data, academic results of the students were attained from the exam coordinator for the running semester. The findings indicated that female students exhibited higher levels of self-motivation as compared to their male counterparts, but there was no discernible difference gap in academic performance. As a recommendation, it was proposed that the university's management introduce initiatives to familiarize students and teachers with self-motivation, enhancing their abilities in goal setting, performance evaluation, and planning. Additionally, the suggestion included the implementation of awareness campaigns and frequent group discussions focused on improving self-motivation abilities.